2021
DOI: 10.1089/pop.2019.0220
|View full text |Cite
|
Sign up to set email alerts
|

Safety Events Associated with Tramadol Use Among Older Adults with Osteoarthritis

Abstract: Tramadol is a low-level opioid increasingly recommended to treat moderate-to-severe acute and chronic pain. Although characterized as having fewer opioid-related adverse events, the longer term safety of tramadol use among older adults has not been thoroughly documented. Thus, the primary objective was to examine the risk of safety events associated with chronic tramadol use compared to other chronic opioid use or no opioids among older adults with osteoarthritis. Safety events considered included: ‡3 emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…These findings, consistent with the substantial evidence of clinical and economic burden of standard of care therapies for treatment of OA, [11][12][13]24 suggest several takeaways and possible areas for further research. Patients initiated on NSAIDs and opioids as part of their OA treatments may experience severe and costly negative health outcomes, particularly in the presence of comorbid conditions in an elderly population, such as cardiovascular disease, hypertension, and kidney disease.…”
Section: Nsaid Tramadolsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings, consistent with the substantial evidence of clinical and economic burden of standard of care therapies for treatment of OA, [11][12][13]24 suggest several takeaways and possible areas for further research. Patients initiated on NSAIDs and opioids as part of their OA treatments may experience severe and costly negative health outcomes, particularly in the presence of comorbid conditions in an elderly population, such as cardiovascular disease, hypertension, and kidney disease.…”
Section: Nsaid Tramadolsupporting
confidence: 70%
“…These negative clinical outcomes include an increased risk of opioid use disorder (OUD), constipation, fatigue, falls, fractures, and nausea, which have all been shown to result in significant humanistic and economic burden. [11][12][13] Given the clinical and economic burden associated with existing pain treatments for OA, there are new drug treatments currently in development that are anticipated to be alternatives to existing treatments. For example, on the short-term horizon, 2 anti-nerve growth factor antibodies, tanezumab and fasinumab, are in active development.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Other side-effects related to opioid use could add even more burden to the NHS. 43,44 Particularly worrisome is the excess mortality associated with opioid use as described in the scientific literature, [45][46][47][48] mainly with strong opioids, which has also been observed in Spanish OA patients receiving strong opioids in the OPIOIDS study. 31,33 (A) (B) We used a real-world approach to project the future opioid burden for OA, based on recent opioid dispensing trends by the AEMPS, anticipated growth in the OA population and the opioid utilization rates observed in the real-world OPIOIDS study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its effectiveness in managing moderate to severe pain, tramadol has been associated with several tissues damage 10 , 12 , 13 . Additionally, chronic use of tramadol was linked to increased hospitalizations due to CVD 34 . Due to the paucity of data describing its actions on the cardiovascular system, we sought to investigate the effect of chronic tramadol treatment on mice heart and aorta.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Solomon and colleagues have reported increased risk for cardiovascular events in arthritis patients taking opioid 32 . Recently, Musich and co-workers demonstrated that 15% of chronic tramadol users had been hospitalized for cardiovascular diseases 34 . Since there is limited literature specifically describing the effects of tramadol on the heart and blood vessels, therefore, it is imperative to characterize the effect of tramadol on the cardiovascular system and the signaling pathways involved.…”
Section: Introductionmentioning
confidence: 99%